A Study on the Indonesian financial sector - Yang, Seunghwon (KDI School, 1998)
This thesis examines the structure of the Indonesian financial sector, the process of reforms, before and after the financial crisis and suggestions to restore the positive functions in the financial industry. The Indonesian financial industry has been predominated by the banking sector. The banking sector consists of the central bank(Bank Indonesia), state-owned commercial banks, private commercial banks, foreign banks, joint venture banks, province development banks and a countless number of Bank Perkreditan Rakyats(villiage banks) The Indonesian financial system has moved toward a more market-based system since the early 1980’s. A series of reforms liberalized the interest rate, entry of new banks, branching, and so on. Reforms have changed the Indonesian economy substantially. As a result, the reforms became one of the most important causes of the Indonesian financial crisis in 1997 because the liberalization occurred too fast compared to the reality of the Indonesian economy. The reforms triggered the increase in the inflow of foreign capital, especially short-term external capital. The Indonesian financial system was not equipped with good infrastructure to protect itself from external shock. The Indonesian foreign exchange rate system had an intervention band and the Indonesian Rupia’s value was closely connected with the US dollar. The external competitiveness of the Indonesian economy was critically impaired when the Chinese Yuan and the Japanese Yen depreciated in mid-1990’s. The weakness of the low external competitiveness snowballed into a deficit of current account and foreign debts. The non-performing loans of Indonesian banks have increased rapidly during the 1990’s due to the lack of capability of the Indonesian financial institutions to analyze customer’s credit and the feasibility of projects. Furthermore, excessive competition among financial institutions, abundant liquidity caused by foreign capital inflow, the principal-agency problem of some private banks of big conglomerates and the long-term economic boom deluded the financial institutions. Indonesia has pursued a balanced budget. The Indonesian government has made its best efforts to decrease the budget deficit. However, it was not effective because there were too many exceptions such as strategic industries, and so on. The Indonesian government requested the IMF rescue package and an IMF rescue package program totalling in the amount of 40 billion US dollars was signed in November 1997. The IMF requested the Indonesian government to implement a fiscal stabilization program and also to restructure the banking sector. The main purposes of reforms were the stabilization of the Rupia and the restoration of confidence in the Indonesian banks from the international financial market. The Bank Indonesia’s banking sector reforms are focusing on re-capitalization, improvement of prudential regulation, reform of the bankruptcy law, merger, suspense and take-over of unsound banks. My suggestions on ways to improve the banking system are as follows. First, the evaluation of the bank personnel should be measured by their performance. Second, the banking system should be transformed from a highly hierarchical generalist organization to a flat expert organization. Third, it is extremely important to establish justice in the economic system. The defaulted borrower should be severely punished.
Thesis(Master) --KDI School:Master of Strategy & International Management,1998